CONSUMER PREFERENCE TOWARDS VISIT INTENTION ON AGRITOURISM DESTINATION - Adizakwan Che Ali,; Hassnah Wee,; Siti Hawa Baharum, (Journal of Islamic, Social, Economics and Development, 2024)
Given the rise in agritourism destinations, it is crucial for anyone working in the sector to understand what influences consumer preference toward visit intention. Understanding further consumer preferences on agritourism will be a valuable step to bridging tourists from urban areas and agritourism sites from rural areas. Therefore, the aim of this study is to explore the consumer preferences towards visit intention on agritourism destinations among visitors who have visited any agritourism site in Malaysia. These factors include facilities, services, and products. 84 respondents who have visited any agritourism site in Malaysia completed a self-administered questionnaire that was meant to collect information and measure respondents' preferences. To test the hypotheses in this study, linear regression analysis was used. The findings demonstrated that the three variables (Facilities, Services, and Products) significantly influence the visit intention on agritourism destinations. The outcome of this study perhaps will help the University College of Agroscience Malaysia (UCAM) to develop a good agritourism development plan effectively and efficiently.